Pertimbangan Kewajiban Prinsip Deklaratif pada Hak Cipta Fotografi Jurnalistik melalui Media Internet - Karuniawan Nurahmansyah (Fakultas Hukum Universitas Islam Jember, 2019)
The principle of declarative at the applications have to give priority to the announcementearly so that the creation of and find refuge , related on permasalah that occurs especially thejournalist they still have not realized and understand the importance of copyright protectionon works journalistic photography , copyright protection arranged on act number 28 years2014 on copyright .In general to get the protection of the law on the rights of copyright is todo recording the creation of on works copyright , but the registration of the work of thecreation of not as evidence that of that work have received the protection of the law , it is justthat as the notions of the preliminary to the process of evidence copyright sengeketa whenyour words come true .Journalist did not yet fully understand his creatures that a workcenters on the rights of journalists and the importance of moral right moral soul because isthe creator of the journalis.Keywords: The declarative, legal protection, copyright, photography journalistic